The Influence of Teaching Talent on Student Learning Outcomes - Pramana, Atan; Syafa'at, Ahmad Mochtar; Khotimah, Khusnul; Susarno, Lamijan Hadi (Jurnal Komunikasi Pendidikan, 2024)
This research aims to examine the influence of teaching talent on student learning outcomes. The research method used is a quasi-experimental research method. The research design uses Factorialized (2x2) Version of the Nonequivalent Control Group Design. The research sample was 140 prospective teacher students at Malang State University, Indonesia. The data analysis technique uses the Analysis of Variances/ANOVA two factor experiment technique. The research conclusion states that differences in teaching talent influence differences in student learning outcomes with an F count of 237,333, significant at p<0.05 and a relatively strong effect size of 0.440. There is a significant difference in the learning outcomes of students who have strong teaching talents compared to the learning outcomes of students who have weak teaching talents. The average value of the subject learning outcomes of the group of students who have strong teaching talents is greater than the average value of the subject learning outcomes of the group of students who have weak teaching talents. Overall, this research contributes to understanding the influence of students' teaching talents in improving learning outcomes which ultimately results in their quality as prospective teachers.